Breakage risk of different sacroiliac screws in unilateral sacral fractures a finite element analysis - Yupeng Ma; Yong Zhao; Dexin Zou; Shengjie Dong; Xiujiang Sun; Gong Cheng; Wei Lian; Yuchi Zhao; Tao Sun; Dan Wang; Shudong Zhang (BMC Musculoskeletal Disorders, 2022)
Abstract Objective To compare the breakage risk of lengthened sacroiliac screws and ordinary sacroiliac screws to treat unilateral vertical sacral fractures and provide a reference for clinical application. Methods A finite element model of Tile C pelvic ring injury (unilateral type Denis II fracture of the sacrum) was produced. The sacral fractures were fixed with a lengthened sacroiliac screw and ordinary sacroiliac screw in 6 types of models. The maximal von Mises stresses and stress distributions of the two kinds of screws when standing on both feet were measured and compared. Results The maximal von Mises stress of the lengthened screw was less than that of the ordinary screw. Compared with ordinary screw, the stress distribution in the lengthened screw was more homogeneous. Conclusions The breakage risk of screws fixed in double segments is lower than that of screws fixed in single segments, the breakage risk of lengthened screws is lower than that of ordinary screws, and the breakage risk of screws fixed in S2 segments is lower than that of screws fixed in S1 segments.